Chemical, biological and nerve gas attacks: need for education among healthcare personnel and medical students; a Swedish regional cross-sectional web-survey - Albert Gyllencreutz Castellheim; Gustav Persson; Juuso Kuikka; Karol Babinski; Yohan Robinson; Fabian Taube (BMC Medical Education)
Abstract Background Chemical, biological and nerve gas events have a significant impact on public health, necessitating proper education and training. This study investigated the educational needs as perceived by two groups, frontline healthcare workers and medical students, in relation to chemical, biological, and nerve gas events. Methods Three distinct web-based cross-sectional surveys were conducted, one each for chemical, biological, and nerve gas events, with each survey following the same structural format including sections on (a) theoretical knowledge assessment, using multiple-choice questions regarding identification, protection, and treatment, (b) perception of threat, using questions based on a 5-point Likert scale to gauge views on threat/preparedness and (c) perception of existing competency, with questions regarding prior education and the need for additional education and training. Results The surveys on chemical, biological, and nerve agents received responses from 44, 36, and 59 participants respectively, comprising both frontline healthcare workers and medical students. The total response rate was approximately 16%. In the theoretical knowledge section of each survey, neither group of participants reached 51% correct answer rate in any of the three surveys. In the section on perception of threat, the percentages of responses in the low half of the Likert Scale were 43.2%, 53.0%, and 96.4% for biological, chemical, and nerve gas surveys, respectively. For the same surveys, 56.8%, 78.7%, and 87.6% of responses were in the middle of the Likert Scale. Regarding perception of competency, 146.2%, 143.1%, and 170.4% of combined responses indicated low existing competency for biological, chemical, and nerve gas surveys, respectively. High and middle ratings for competency were low across all surveys. The perception of need for education were high in the high half and low in the low half of the Likert Scale. The were no statistically significant differences across the sections among the study groups. Conclusions The results indicate a widespread tendency to downplay the presence of significant threat and a perception of low existing competency. There is a broad agreement on the need or education and training in managing events of chemical, biological, and nerve gas agents, for frontline healthcare personnel as well as medical students in Sweden.